2015
DOI: 10.1002/cctc.201402943
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Roles of Imidazolium Ionic Liquids in Transition‐Metal Catalysis: The Palladium‐Catalyzed Telomerization of 1,3‐Butadiene with Acetic Acid

Abstract: The telomerization of 1,3‐butadiene with acetic acid catalyzed by palladium(II) acetate associated with a series of phosphines in 3‐(2‐methoxyethyl)‐1‐methylimidazolium acetate was used to investigate the role of the ionic liquid. The ionic liquid plays multiple roles in this reaction as it acts as the solvent, stabilizer, ligand, and cocatalyst. The reaction performed in the presence of Dan2phos, a trifluoromethylated sulfonated triarylphosphine, at 100 °C for 24 h gave a turnover number of 14 600 with 89 % s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The only exception to this that we are aware of is the telomerization of 1,3‐butadiene with acetic acid, as investigated by Dupont et al in 2015 . The reaction yields 2,7‐octadienyl acetate, as is shown in Scheme .…”
Section: Nucleophilesmentioning
confidence: 98%
“…The only exception to this that we are aware of is the telomerization of 1,3‐butadiene with acetic acid, as investigated by Dupont et al in 2015 . The reaction yields 2,7‐octadienyl acetate, as is shown in Scheme .…”
Section: Nucleophilesmentioning
confidence: 98%
“…Recently, we reported that the addition of an ionic liquid that contains the 1,3‐dialkylimidazolium cation to the telomerization reaction of butadiene and acetic acid has a remarkable effect in the Pd/phosphine catalyst performance . However, it is known that the addition of this type of ionic liquids to the telomerization reaction of 1,3‐butadiene with methanol leads to the complete deactivation of the catalyst, likely by the formation of a catalytically inactive palladium‐carbene species.…”
Section: Resultsmentioning
confidence: 99%
“…[16,25] Recently,w er eportedt hat the addition of an ionic liquid that contains the 1,3-dialkylimidazolium cation to the telomerization reactiono fb utadiene and acetic acidh as ar emarkable effect in the Pd/phosphine catalyst performance. [26] However,i t is knownt hat the addition of this type of ionic liquids to the telomerization reactiono f1 ,3-butadiene with methanol leads to the complete deactivation of the catalyst, [27] likely by the formation of ac atalytically inactive palladium-carbene species. The formation of this speciesr equires ab asic mediumt od eprotonate the C2ÀHp osition of the imidazolium cation (Scheme 5), [28][29][30] such as that provided by the methoxide used as cocatalyst in the telomerization with methanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ILs are widely used in the chemical industry, 8 catalysis, 9 biocatalysis, 10 extraction processes, 11 the obtention and purification of biological components, 12 and other applications. 13 For a long time, these ionic fluids have actually been claimed to be the solvents of the future 14–16 because they represent a plausible alternative towards environmental acceptability.…”
Section: Introductionmentioning
confidence: 99%